Peningkatan Kapasitas Ekspor UMKM Banyumas Melalui Coaching Clinic - Srirejeki, Kiky; Afwa, Ulil; Khairurrizqo, Khairurrizqo (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Banyumas possess considerable potential to contribute to the regional economy through export activities. However, numerous MSMEs encounter significant challenges, particularly in understanding export procedures, adhering to international quality standards, and developing effective global marketing strategies. Our community engagement initiative aims to enhance the preparedness of Banyumas MSMEs to access international markets through a structured coaching clinic program, conducted in collaboration with Association of Small and Medium Enterprises and Industries of Banyumas (ASPIKMAS) The implementation methodology encompasses comprehensive training sessions and targeted mentoring programs. The anticipated outcomes include an improvement in the knowledge and competencies of MSME actors regarding export processes, as well as an expanded understanding of international market opportunities. It is expected that this initiative will significantly enhance the global competitiveness of Banyumas MSMEs, thereby fostering economic growth and sustainability in the region.